Abra a roda tin dô lê lê: dimensão religiosa nas brincadeiras de roda entre crianças de 4 a 6 anos - Poyares, Mônica Amaral Melo (2006)
Our goal was to study the Circle Time games as a religious experience in school. The contribution of this work is the possibility of an alternative practice in Religious Studies with 4-6 years old children. To perform it, we ve made an approximation between Sacred Circular Dances, first studied by Bernhard Wosien, and traditional Circle Time games, selecting the elements common to both practices. In 2004, we observed a group of 24 children and two teachers, and the experience was recorded. To understand activity s symbolic language, we studied Jung s concepts of self, ego, collective unconscious and archetypes. We also used the concepts of Sacred Space, defined by New Age followers and Hierophany, conceived by Mircea Eliade. Because these activities are treated as rites, Victor Turner s concepts of thresholdness and communitas were helpful to understand the rituals´ steps and their consequences. Vygotsky contributed with his vision of mediation and proximal development zone to explain why Circle Time games are chosen to cooperate with the knowledge of the Religious Studies contents. Among the possible subjects, we chose rites and their symbolic language. At last, we interpreted the recorded activities we mentioned before. We concluded that, considering the way they were treated in this work, the Circle Time games can be one more instrument to teach Religious Studies. Besides, they are able to improve children s relationships as they have much in common with the initiation rites